Chemical composition and glucose uptake effect on 3T3-L1 adipocytes of Ligustrum lucidum Ait. flowers - Lili Cui; Jinmei Wang; Mengke Wang; Baoguang Wang; Zhenhua Liu; Jinfeng Wei; Wenyi Kang (Food Science and Human Wellness)
Ligustri lucidi Fructus is a traditional Chinese medicine and possesses various bioactivities, including hypoglycemic effect. Ligustrum lucidum Ait flowers are poorly investigated. Thus, we hypothesized that L. lucidum flowers also could have hypoglycemic effect. Chemical composition and glucose uptake effect of L. lucidum flowers on 3T3-L1 adipocytes were investigated. In this study, the components of L. lucidum flowers were investigated by various chromatographic and spectroscopic methods and the effects of L. lucidum flowers on the induction of glucose uptake were investigated by 3T3-L1 adipocytes. Seven compounds were isolated and identified from L. lucidum flowers, including ursolic acid (1), kaempferol-7-O-α-l-rhamnoside (2, KR), β-sitosterol (3), β-daucosterol (4), kaempferitrin (5, KF), 10-hydroxy oleuropein (6, HO), and kaempferol-3-O-β-d-glucopyranoside-7-α-l-rhamnopyranoside (7, KGR). The results of glucose uptake showed that total extract (TE), KR, KF and HO from L. lucidum flowers significantly enhanced glucose uptake. This study demonstrated that compounds 2, 5-7 were isolated for the first time from this plant and compounds 2 and 7 were isolated for the first time in genus Ligustrum, L. lucidum flowers, KR, KF and HO may possess potential hypoglycemic effect.